The Effect of Special Allocation Funds and Regional Original Income on Poverty in Cities/Regencies of West Kalimantan Province - Panggabean, Jannes Samuel Elfronzo Abhimael; Kotte, Jeniwanti Carolina; Kaloeti, Ade Kristianus (EQUILIBRIUM - Jurnal Bisnis dan Akuntansi, 2023)
The study analyzes how the Special Allocation Fund (SAF) and Regional Original Income (ROI) impact poverty in cities/districts in West Kalimantan. It utilizes secondary panel data from 12 districts and two cities in the region between 2018-2022. The findings suggest that SAF Nonfisik has no effect on poverty, while ROI has a negative impact. The study concludes that local governments should evaluate the effectiveness of using transfer funds from the central government to ensure effective poverty alleviation efforts.